Skogsbete och fäbodars betydelse i norra Jämtland : en jämförande intervjustudie - Hemmingsson, Nanna; Espvall, Jessica (SLU/Dept. of Forest Ecology and Management, 2025)
Shielings and pasture (forest) grazing have been utilized for a long time in various parts of Sweden. During the 18th and 19th centuries, the use of shielings was a vital and regulated part of the agricultural system, especially in northern Sweden. Life on these farms gave rise to a unique culture bases on the practical needs that had to be met. The purpose of this study is to analyze forest grazing and shielings in northern Jämtland (county) during the mid-20th century and the 2020s. The study focuses on four themes; labor, animal husbandry, incentives for shielings and the forest. The material of the study was collected through qualitative interviews with individuals who have conducted or have experience with shielings in the mid 20th century and/or in the 2020s. The results show that shieling management differed between the two periods. Generally, it was primarily the women in the family who managed the shieling and the work there during the mid-20th century. This distribution has changed in the 2020s. Throughout both periods, fjällkor (mountain cattle) were consistently the main livestock found among the informants. Furthermore, the results indicate that the workload involved with running the shielings is significant, and that routines are important in both periods. The incentives for bringing livestock to the shielings were fundamentally similar in both periods but manifested differently. Additionally, the results reveal that grazing around the shieling-ground has led to a special vegetation composition in the forest that depends on continuous grazing. In the discussion, the results from the different periods are compared and contrasted with other studies. The division of labor on shielings has been predominantly female since at least the last century. In Europe, similar transhumance systems have instead been male dominated. The characteristic calls (herding calls) that arose from working on shielings were present in both the mid-20th century and the 2020s. Finally, the choice of methods and the execution ...